2014
DOI: 10.3329/dujps.v12i2.17617
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antidiabetic activities of Alangium salvifolium and Bombax ceiba

Abstract: ABSTRACT:In the present study, a methanol extract of flower of Alangium salvifolium (AS) and bark of Bombax ceiba (BC) were evaluated for its antioxidant and antidiabetic activities. Both methanol extracts exhibited DPPH free radical scavenging activity and reducing power activity in dose dependent manner. Continuous administration for of methanol extracts of AS for seven days significantly decreased blood glucose level than BC in alloxan induced diabetic rats at a dose of 200 mg/kg body weight. The IC 50 valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(8 reference statements)
1
3
0
Order By: Relevance
“…The extract was able to protect from the reduced longevity and to diminish whole body glucose levels induced by high glucose exposure. A similar effect has been observed in the alloxan-induced diabetic rats treated with B. ceiba bark methanolic extract [ 35 ]. Furthermore, the alcoholic extract of C. pentandra , a species taxonomically related to C. speciosa which is commonly used in North Africa, has been used to control hyperglycemia in diabetic patients [ 36 ].…”
Section: Discussionsupporting
confidence: 79%
“…The extract was able to protect from the reduced longevity and to diminish whole body glucose levels induced by high glucose exposure. A similar effect has been observed in the alloxan-induced diabetic rats treated with B. ceiba bark methanolic extract [ 35 ]. Furthermore, the alcoholic extract of C. pentandra , a species taxonomically related to C. speciosa which is commonly used in North Africa, has been used to control hyperglycemia in diabetic patients [ 36 ].…”
Section: Discussionsupporting
confidence: 79%
“…They used B. ceiba whole plant extract that showed higher scavenging activity against DPPH with IC 50 value of 68 μg / ml. In another study Zahan et al (2013) while studying the methanolic extract of bark of B. ceiba demonstrated good DPPH radical scavenging activity having IC 50 32.1 μg / ml. Antioxidant activity has been suggested to be associated to reducing power (Zengin et al 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Jain et al (2011) described in their study that the methanolic extract of root demonstrated dose-dependent reduction from Fe³ + to Fe² + with highest absorbance of 1.11 at 500 µg / ml. In another work done by Zahan et al (2013) on methanolic extract of bark of B. ceiba showed that the extract possesses adequate reducing activity. Leafy and root vegetables contain large quantities of nitrite that is extremely toxic.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation